Deployment behavior control using cables and bi-shape memory alloy convex tape booms. (July 2017) - Katsumata, Nobuhisa; Kume, Masaru; Higuchi, Ken
This study aims to demonstrate the synchronous and stable deployment of a newly proposed boom system that consists of cables, a rotary damper, and shape memory alloy with a memorized convex tape shape. Through a shaft, a rotary damper is connected to a reel, and cables wound around the reel are connected to the shape memory alloy boom tips. The deployed part consists of bi-shape memory alloy convex tape booms in which two shape memory alloy convex tapes are combined to form a convex lens cross section, and the outside of the bi-shape memory alloy convex tape is wrapped by a sheet-type heater and polyimide film. The boom is deployed using only the shape recovery force of the shape memory alloy. By installing cables and a rotary damper, the deployment behavior of each boom is controlled, and each boom is deployed synchronously owing to the resistance force of the damper to a leading deploy boom. Moreover, the structural stiffness control concept of the proposed shape memory alloy bi-convex tape boom is discussed considering that Young's modulus becomes almost half in the martensitic phase.